Antibacterial activity of In2O3 nanopowders prepared by hydrothermal method. (2021) - Husain, Zahra A.; Majeed, Alaa A.; Rasheed, Rashed T.; Mansoor, Hadeel S.; Hussein, Nehia N.
Abstract: Indium oxide (In2 O3 ) nanopowders were prepared using hydrothermal method and the nanopowders were further annealed at temperature of 400 °C. The synthesized powders were characterized by different methods such as, FT-IR spectrometer, X-ray Diffraction (XRD), spectroscopy of Ultra-violet/visible, Scanning Electron Microscopy (SEM), and the microscopic techniques of Atomic Force Microscopy (AFM). The effect of In2 O3 nanopowder was tested against two types of pathogenic bacteria; Staphylococcus aureus (G+ve), and E. coli (G−ve). The results demonstrated that the In2 O3 nanopowders have a powerful antibacterial activity and, hence, can be used in the treatment of infections with both of these bacterial species.